Concurrent validity of Open‐Ended Functional Assessment Interviews with functional analysis. (22nd December 2021) - Gossou, Komlantse M.; Lanovaz, Marc J.; Giannakakos‐Ferman, Antonia R.
Abstract: Open‐Ended Functional Assessment Interviews have limited empirical support for their concurrent validity with functional analysis. To address this issue, we conducted a study wherein 176 independent behavior analysts relied on data collected using Open‐Ended Functional Assessment Interviews to identify the function of challenging behavior in four children with autism. Then, we compared the results of their analyses with those of a traditional functional analysis. Our results showed that the conclusions drawn by behavior analysts using the Open‐Ended Functional Assessment Interviews corresponded with the outcomes of functional analyses in 74% of cases. These findings suggest that the Open‐Ended Functional Assessment Interview may inform functional analyses to develop initial hypotheses.